Evaluasi Benchmarking sebagai Strategi dalam Meningkatkan Keunggulan Bersaing dan Kinerja Bisnis - Anisah, Anisah (Universitas Batanghari Jambi, 2024)
This research aims to look at the influence of benchmarking on competitive advantage and the influence of both on performance. The research method used is a quantitative descriptive method with a sample of 115 businesses at the middle level. The data collection technique used in this research is a questionnaire and the data analysis technique uses the SEM method. The results of this research prove that there is a positive and significant influence of benchmarking on competitive advantage and competitive advantage on business performance, but benchmarking does not have a positive impact on business performance, unless mediated by the construct of competitive advantage.